Biochemistry. Module 1. Common regularities of metabolism and energy exchange in humans. Metabolism of carbohydrates, lipids and amino acids and its regulation. Laboratory manual for independent work at home and in class, preparation for licensing examination “KROK-1” for students of 2-d year study Specialty: 222 “Medicine” - Aleksandrova, K. V.; Krisanova, N. V.; Rudko, N. P.; Ivanchenko, D. G.; Александрова, Катерина Вячеславівна; Крісанова, Наталія Вікторівна; Рудько, Наталія Петрівна; Іванченко, Дмитро Григорович (Запорізький державний медичний університет, 2017)
This manual is recommended to use for students of II International faculty (the second year of study) for independent work in Biochemistry discipline at home and in class.